Metabolite profiling in arabidopsisthaliana with moderately impaired photorespiration reveals novel metabolic links and compensatory mechanisms of photorespiration - Timm, Stefan; Nunes-Nesi, Adriano; Florian, Alexandra; Eisenhut, Marion; Morgenthal, Katja; Wirtz, Markus; Hell, Rüdiger; Weckwerth, Wolfram; Hagemann, Martin; Fernie, Alisdair; Bauwe, Hermann (Metabolites, 2021)
Photorespiration is an integral component of plant primary metabolism. Accordingly, it has been often observed that impairing the photorespiratory flux negatively impacts other cellular processes. In this study, the metabolic acclimation of the Arabidopsisthaliana wild type was compared with the hydroxypyruvate reductase 1 (HPR1; hpr1) mutant, displaying only a moderately reduced photorespiratory flux. Plants were analyzed during development and under varying photoperiods with a combination of non-targeted and targeted metabolome analysis, as well as 13C- and 14C-labeling approaches. The results showed that HPR1 deficiency is more critical for photorespiration during the vegetative compared to the regenerative growth phase. A shorter photoperiod seems to slowdown the photorespiratory metabolite conversion mostly at the glycerate kinase and glycine decarboxylase steps compared to long days. It is demonstrated that even a moderate impairment of photorespiration severely reduces the leaf-carbohydrate status and impacts on sulfur metabolism. Isotope labeling approaches revealed an increased CO2 release from hpr1 leaves, most likely occurring from enhanced non-enzymatic 3-hydroxypyruvate decarboxylation and a higher flux from serine towards ethanolamine through serine decarboxylase. Collectively, the study provides evidence that the moderate hpr1 mutant is an excellent tool to unravel the underlying mechanisms governing the regulation of metabolic linkages of photorespiration with plant primary metabolism.